Popular fiction and white extremism: Neo‐Nazi ideology and medievalist crime fiction. Issue 11 (12th October 2022) - Young, Helen; Downes, Stephanie
Abstract: Dystopian near‐future fantasies of violent white revolution and genocide—most infamously, William L. Pierce's The Turner Diaries (1978)—are the most well‐known and studied fictions by white extremists. They are, however, not the only genre through which the extreme far‐right engage with popular culture. In this article, we explore how popular historical fictions can accomodate white extremist presence and propagandising. We analyse generic conventions in the medieval murder mystery The Black Flame (2001) by self‐identified neo‐Nazi Harold A. Covington (1953–2018), showing that the book shares trends and tropes with contemporary medievalisms, including in historical crime fiction and other popular genres and media. By focussing on these conventions, we seek common places in the popular that can, paradoxically, create space for the fringe extreme.